Character association and genetic gain of nine agronomic traits of F1 populations in onion (Allium cepa L.) - Deb, A. C.; Ara, R. (International Journal of Horticultural Science, 2021)
F1 populations of half diallel cross were considered for this investigation. Phenotypic component of variation (s2P) was higher than genotypic (s2G), interaction ((s2I) and within error (s2w) components of variation. Trait bulb weight showed the highest values for s2P, s2G, s2I and s2w. The noticeable amount of phenotypic, genotypic, interaction and within error covariation was found in the combination of BW×BY, possibly indicating wide scope of selection for this pair of characters. Genotypic correlations were higher than the respective phenotypic correlations. This situation was also marked in the path coefficient analysis. Bulb yield/plot showed highly significant and positive correlation coefficient with other characters both at phenotypic and genotypic levels. When all the nine characters were included in an index, it exhibited the highest genetic gain as percentage. When a combination of two or more characters was studied in a function, the efficacy was higher than that of direct selection for bulb yield. The combination of five, six, seven or eight characters showed higher percentage of expected gain. Due to significantly correlated with BY and having high positive direct effect at phenotypic level characters viz., LL, BW, PH and NLs is considered as primary yield components. Again combinations of these four characters gave the commendable expected genetic gain of 330.7290% may be considered as important selection index for this material.